2023
DOI: 10.1007/s41666-023-00126-5
|View full text |Cite
|
Sign up to set email alerts
|

The IHI Rochester Report 2022 on Healthcare Informatics Research: Resuming After the CoViD-19

Abstract: In 2020, the pandemic spread worldwide in an unexpected way and suddenly modified many life issues, including social habits, social relationships, teaching modalities, and more. Such changes were also observable in many different healthcare and medical contexts. Moreover, the pandemic acted as a stress test for many research endeavors, and revealed some limitations, especially in contexts where research results had an immediate impact on the social and healthcare habits of millions of people. As a result, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 99 publications
0
1
0
Order By: Relevance
“…Table 3 reports an example of some of these practices and lessons. Finally, observations about post-pandemic research topics can be found in [ 92 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 3 reports an example of some of these practices and lessons. Finally, observations about post-pandemic research topics can be found in [ 92 ].…”
Section: Discussionmentioning
confidence: 99%
“…Table 3 reports an example of some of these practices and lessons. Finally, observations about post-pandemic research topics can be found in [92]. The progressive transition from paper-based campaigns to a digital system is essential to allow all actors to have real-time data in response to the speed of the spreading Improves the speed of the response to the pandemic…”
Section: Discussionmentioning
confidence: 99%